'It's cheaper than a dead cow': Understanding veterinary medicine use on dairy farms. (August 2021) - Rees, Gwen M.; Reyher, Kristen K.; Barrett, David C.; Buller, Henry
Abstract: This study offers a detailed and original assessment of the practices of prescription veterinary medicine use on UK dairy farms. The emergence of antimicrobial resistance as a global threat has necessitated an increasing focus on medicine use in agriculture. While an abundance of studies have recently emerged to demonstrate and evaluate strategies for medicine reduction, this paper seeks to understand the context and the on-farm culture within which treatment practices occur on a sample of UK dairy farms. Arguing that the experiential knowledge, on-farm culture and informal information flows are as important as 'science' in the practice of treatment decision making and drawing on extensive participant observation fieldwork combined with semi-structured interviews, this paper identifies and discusses three key themes that develop and, in places, challenge our current understanding of farmer treatment practices. These areas - treatment knowledge and understanding, a duty of care and autonomy of treatment practice - are seen to have complex effects on the use of veterinary medicines in dairy cattle and, as such, highlight critical areas for further research and opportunities for policy interventions aimed at improving responsible medicine use. Highlights: Farmers construct their own narratives of disease and treatment, based on experiential and experimental knowledges. Uncertainty remains a key element of treatment decision-making, which can manifest as risk-averse behaviour. Farmers are strongly motivated to treat by a sense of duty to the wellbeing of the animals for which they are responsible. A perceived lack of autonomy with regard to treatment decisions directly affected dairy farmers' medicine use behaviours.